1949
DOI: 10.1021/ja01170a019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Equilibrium Constants for the Isomeric Hexanes

Abstract: In the course of the development of the naphtha isomerization process1•2 the equilibrium constants for the isomeric hexanes were determined. Although the equilibrium constants for butanes and pentanes3•4 have been repeatedly investigated, few experimental data have appeared for the hexanes.Two papers5•6 have appeared on the direct experimental determination of the equilibrium constants for the hexanes but they were limited to 25 and 80°, respectively. The hexane equilibria were calculated over a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1949
1949
1971
1971

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…It was found that the" experimentally determined equilibrium values differed from those calculated from the data of Rossini (72); the concentration of 2,2dimethylbutane at equilibrium being lower than the calculated equilibrium value. This observation has also been noted by other investigators (7,77,74). The experimentally determined equilibrium values used in these studies are given in Table IV.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…It was found that the" experimentally determined equilibrium values differed from those calculated from the data of Rossini (72); the concentration of 2,2dimethylbutane at equilibrium being lower than the calculated equilibrium value. This observation has also been noted by other investigators (7,77,74). The experimentally determined equilibrium values used in these studies are given in Table IV.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…carbon steel bomb equipped with, a mechanical stirrer operating at 1725 r.p.m. (4). After settling, the hydrogen fluoride extract layer was separated from the supernatant hydrocarbon layer by withdrawal through a valve at the bottom of the reactor.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Work on the direct determination of equilibrium composition (3,4) in the 100°to 400°F. range has shown that the calculated equilibria do not correspond to the observed composition.…”
mentioning
confidence: 99%